Diagnóstico sectorial de la actividad de peluquería y otros tratamientos de belleza en el distrito 11D06, provincia de Loja. - Calva Camacho, Julieth de Lourdes (2024)
The sectoral diagnosis provides information on the organisational performance of the companies of an economic activity, with the aim of identifying the strengths and weaknesses of the sector to enable informed decision-making and contribute to the success of the sector. In this way, the research aims to carry out a sectoral diagnosis of the activity of hairdressing and other beauty treatments in district 11D06, province of Loja; for which 52 hairdressing salons were surveyed within the geographical limits of the urban parishes of district 11D06, by means of the methodology of transversal approach by quantitative and qualitative methods; to collect information necessary for the study, the technique of winsorizing was used to minimise the effect of outliers. Thus, the relevance of the sector was defined by its contribution to beautify the appearance and raise self-esteem in the community, and thus establish the success factors such as: competent and trained staff, quality of care, variety of services, marketing, continuous improvement and innovation, infrastructure and adequate financial management. From which the industry averages were determined, both financial and non-financial indicators such as ROA 37 %, profit margin 43 % and debt ratio 64 %, customer retention 80 % and diversification of services 18 %, among others. It is concluded that of the total number of hairdressers surveyed more than 50% are above average, the sector in general shows positive indicators, reflecting its competitiveness and performance.